2014
DOI: 10.1039/c4tb01106f
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic biopolymer nanogels via biological assembly for vectoring delivery of biopharmaceuticals

Abstract: Biopolymer-based nanogels have great potential in the field of tissue regenerative medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Fan et al. have developed a magnetic biopolymer based nanogels chitosan and heparin by specific nucleobase pairing between thymine and adenine via the hydrogen bonding for vectoring delivery of bone morphogenetic protein 2 (BMP‐2) . The encapsulation of IONPs gave the magnetic biopolymer nanogels magnetic responsibility.…”
Section: Magnetic‐based Drug Delivery For Bone Growthmentioning
confidence: 99%
“…Fan et al. have developed a magnetic biopolymer based nanogels chitosan and heparin by specific nucleobase pairing between thymine and adenine via the hydrogen bonding for vectoring delivery of bone morphogenetic protein 2 (BMP‐2) . The encapsulation of IONPs gave the magnetic biopolymer nanogels magnetic responsibility.…”
Section: Magnetic‐based Drug Delivery For Bone Growthmentioning
confidence: 99%
“…Biopolymers owing to their biodegradable biocompatible and safe characteristics have gained widespread utilization in tissue engineering applications [135][136][137][138]. Fan et al (2014) reported preparation of a biopolymer based magnetic nanogels of 109.4 nm by coupling heparin and CHI with adenine and thymine nucleobases and subsequent encapsulation of Fe 3 O 4 magnetic nanoparticles in self-assembled nanogels [139]. In vitro release of bone morphogenetic protein 2 (BMP-2) as growth factor in physiological conditions and their cytotoxicity to MG-63 bone osteosar- Beside single targeting and stimulus directed control over the release behaviors of micro nanogels, development of particles with combined multiple targeting and stimuli responsivity gave rise to emergence of multifunctional captivating materials that provide more stable and controlled delivery to target sites of interest and achieve elongated systemic circulation half-lives.…”
Section: Stimuli Responsive Micro/nanogels and Targeted Drug Deliverymentioning
confidence: 99%
“…The biological self-assembly PEG hydrogel system is established by the Watson-Crick base pairing between thymine (T) and adenine (A) via the hydrogen bonding (Figure 2a). Compared with linear PEG, multi-arm star-shaped PEG has the nature to induce stereo-complex formation, which shows promise in biomedically relevant hydrogel systems (M. Fan, Yan, Tan, Miao et al, 2014;H. Tan, Xiao et al, 2012).…”
Section: Nucleobase Pairingmentioning
confidence: 99%